Down-regulation of ABCB1 transporter by atorvastatin in a human hepatoma cell line and in human peripheral blood mononuclear cells - Rodrigues, Alice Cristina; Curi, Rui; Britto, Luiz R.G.; Rebbechi, Ivanise M.M.; Hirata, Mario H.; Bertolami, Marcelo C.; Bernik, Marcia M.S.; Dorea, Egidio L.; Hirata, Rosario D.C. (Biochimica et biophysica acta, 2006)
Purpose. The effect of atorvastatin, an HMG-CoA reductase inhibitor, on expression and activity of the drug transporter ABCB1 in HepG2 cells and peripheral blood mononuclear cells (PBMCs) was examined. Methods. Localization and expression of ABCB1 in hepatocytes was examined by indirect immunofluorescence. Expression of ABCB1 mRNA and ABCB1 activity were examined in atorvastatin-treated and control cells and PBMCs using real-time PCR and Rhodamine 123 efflux assay. Results. Immunohistochemical analysis revealed that ABCB1 is located at the apical membrane of the bile canaliculi. Atorvastatin at 10 and 20 μM up-regulated ABCB1 expression resulting in a significant 1.4-fold increase of the protein levels. Treatment of HepG2 cells with 20 μM atorvastatin caused a 60% reduction on mRNA expression ( p < 0.05) and a 41% decrease in ABCB1-mediated efflux of Rhodamine123 ( p < 0.01) by flow cytometry. Correlation was found between ABCB1 mRNA levels and creatine kinase ( r = 0.30; p = 0.014) and total cholesterol ( r = − 0.31; p = 0.010). Conclusions. Atorvastatin leads to decreased ABCB1 function and modulates ABCB1 synthesis in HepG2 cells and in PBMCs. ABCB1 plays a role in cellular protection as well as in secretion and/or disposition, therefore, inhibition of ABCB1 synthesis may increase the atorvastatin efficacy, leading to a more pronounced reduction of plasma cholesterol.